Islamic Law and The Politics of Nation-State: Debating Citizenship Fiqh Through The Al-Maskut 'Anhu Discourse - Prihantoro, Hijrian Angga; Hasan, Noorhaidi; Masrukhin, Mohammad Yunus (AHKAM : Jurnal Ilmu Syariah, 2023)
The jurisprudential aspects of citizenship (known as fiqh al-muwāṭanah), emerging from the realm of ijtihād, have sparked considerable debate due to their theoretical nature. The term "citizenship fiqh" is not explicitly mentioned in the Quran or Sunna; consequently, it lacks demonstration within the context of the Prophetic era. This study aims to delve into citizenship fiqh by examining the discourse known as al-maskūt' anhu, shedding light on how Muslim scholars validated novel findings. To achieve this objective, the paper employs Foucault's critical discourse analysis theory to showcase that each era holds the prerogative to embrace distinct political systems and legal frameworks. Adopting a qualitative approach and drawing from various literary sources, this research proposes embracing the al-maskūt 'anhu discourse as the fundamental concept underpinning studies on citizenship within Islamic legal thought. This investigation discerns that citizenship fiqh embodies a blend of political and religious engagement. It can be effectively harnessed as a mechanism of legal governance during the nation-state era, provided it effectively contributes to the populace's well-being and fosterssocial equity. Abstrak: Aspek-aspek fikih kewarganegaraan (fiqh al-muwāṭanah), yang muncul dari ranah ijtihad, memicu banyak perdebatan karena sifat teoretis nya. Terminologi “fikih kewarganegaraan” tidak ditemukan secara eksplisit dalam Al-Quran atau Sunah, dan sebagai konsekuensinya, tidak terdemonstrasi kan dalam konteks era kenabian. Artikel ini bertujuan untuk menggali konsep fikih kewarganegaraan melalui diskursus al-maskūt ‘anhu, dan menyoroti bagai mana para sarjana muslim memvalidasi temuan-temuan baru. Artikel ini meng guna kan teori analisis wacana kritis Foucault untuk menunjukkan bahwa setiap era memiliki hak prerogatif untuk mengadopsi sistem politik dan kerangka hukum yang berbeda. Dengan menggunakan pendekatan kualitatif dan menganalisis berbagai sumber literatur, penelitian ini merekomendasikan diskursus al-maskūt 'anhu sebagai konsep dasar yang mewadahi studi kewarganegaraan dalam pemikiran hukum Islam. Studi ini menemukan bahwa fikih kewarganegaraan, pada dasarnya, mencakup perpaduan diskursif antara aspek politik dan agama. Hal ini dapat dimanfaatkan secara efektif sebagai mekanisme tata kelola hukum pada era negara-bangsa, dengan catatan dapat berkontribusi terhadap kesejahteraan masyarakat dan mendorong kesetaraan sosial.